Josef Michl. Issue 37 (2nd October 2018) - Unknown
Abstract: "The Michl group deals with Singlet fission for solar cells, molecular rotors, direct alkylation of gold surfaces, and fluorinated carborane anions." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800507 . Abstract : "The Michl group deals with Singlet fission for solar cells, molecular rotors, direct alkylation of gold surfaces, and fluorinated carborane anions." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800507 .